Antibacterial Potency and Phytochemical Screening of the Bark of Terminalia catappa Against some Clinical Isolates - Ajiboye A.E.; Babatunde S.K; Adedayo M.R; Adetumbi M.A; Ajuwon I.B; Ajasegun T.A (International Journal of Phytomedicine, 2016)
To evaluate the antibacterial properties of ethyl acetate and aqueous extracts of the bark of Terminalia catappa against some clinical isolates. The antibacterial activity of the T. catappa bark extracts was evaluated against five bacterial clinical isolates which are Escherichia coli, Staphylococcus aureus, Salmonella typhi, Pseudomonas aeruginosa and Klebsiella pneumoniae using agar-well diffusion method. The minimum inhibitory concentration was done by the broth dilution method. Broad spectrum antibiotics were used as positive control for the antibiotic sensitivity test. Qualitative and quantitative phytochemical screening of T. catappa bark were carried out using standard methods. However, ethyl-acetate and aqueous extracts of Terminalia catappa bark both showed that K. pneumoniae was more sensitive compared with E. coli, S. typhi, S. aureus and P. aeruginosa. Antibacterial activity of the ethyl acetate and aqueous extracts showed the value range from 10.33 ± 0.58 mg/ml to 9.33 ± 0.60 mg/ml. Ethyl-acetate extract showed minimum inhibitory concentration (MIC) at 80 mg/ml while the aqueous extract shows MIC at the concentration of 100 mg/ml. However the minimum bactericidal concentration (MBC) of ethyl-acetate extract against the clinical isolates was at the concentration of 100 mg/ml while there was no minimum bactericidal concentration (MBC) for the aqueous extract. Phytochemical screening shows the presence of saponins, glycosides, and alkaloids, in larger quantity while flavonoids, tannins, and steroids in smaller quantity. This study indicates that the extracts were efficacious and can be used for the management of diseases caused by the tested organisms. Results obtained support the use of this plant as use in traditional medicine and support that the plant extracts possess compounds with good antimicrobial properties that can be used as antimicrobial agents in the search for new antimicrobial drugs.